Enhancing Fashion Inventory Reporting: How Accounting Information Systems Improve Report Effectiveness in Bandung - Adam Ramdani; Tri Ningsih (Acman: Accounting and Management Journal, 2026)
Standardized inventory management often fails to meet the dynamic demands of the fast-fashion industry, leading to inefficiencies. This study investigates the critical challenges surrounding inventory effectiveness within a prominent fashion company based in Bandung, Indonesia. This research aims to examine and evaluate the specific extent to which an Accounting Information System (AIS) for inventory influences overall inventory effectiveness. The study utilized a quantitative survey approach. The researchers collected primary data from a targeted sample of warehouse staff, production administrators, and supply chain personnel using a simple random sampling technique. The study employed simple linear regression analysis to analyze the quantitative data and test the hypothesis regarding the relationship between the two variables. The statistical analysis reveals that the implementation of an inventory AIS exerts a significant positive impact on inventory effectiveness. Well-integrated information systems directly optimize stock control and reduce operational errors. While previous studies often focus on general corporate retail, this research isolates the unique operational ecosystem of a Bandung-based fashion hub. It highlights how localized supply chain dynamics adapt to modern digital accounting frameworks. These findings imply that fashion enterprises must prioritize investments in robust, tailored AIS modules. Doing so will streamline supply chain communication, minimize stock discrepancies, and ultimately enhance market competitiveness.